Date (Phoenix dactylifera L.) fruits and seeds nanotechnology: A mini review - A. S. M. Ammar (Пищевые системы)
Nanotechnology is widely used in various sectors, and the increased interest in using nanoparticles in food technology is very clear. In this article, the history of dates and date production in Egypt was described. The anatomy of date fruit, classification of dates according to the moisture content, maturity stages, quality indices, and chemical composition, bioactive components and nutrients of dates, and the glycemic index and glycemic load of different varieties of dates worldwide were reviewed. The most recent date fruit nanoparticles (DFNPs) products and their applications for human health, such as anticancer, antimicrobial, and anti-fibrotic activities, were presented. The nutritional value of date kernels and their uses is of great interest in producing functional foods. Therefore, special emphasis has also been given to the novel date seed nanoparticles (DSNPs) products and their utilization. The role of these nanoparticles in nonfood sectors, such as yielding biodiesel, good thermal insulation in buildings, nanofillers as reinforcement materials in plastic, and as bio-adsorbent of pigments, was also considered.